2014
DOI: 10.1002/bit.25479
|View full text |Cite
|
Sign up to set email alerts
|

D‐Amino acids inhibit initial bacterial Adhesion: Thermodynamic evidence

Abstract: Bacterial biofilms are structured communities of cells enclosed in a self-produced hydrated polymeric matrix that can adhere to inert or living surfaces. D-Amino acids were previously identified as self-produced compounds that mediate biofilm disassembly by causing the release of the protein component of the polymeric matrix. However, whether exogenous D-amino acids could inhibit initial bacterial adhesion is still unknown. Here, the effect of the exogenous amino acid D-tyrosine on initial bacterial adhesion w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 49 publications
0
26
0
Order By: Relevance
“…The destructive effect of non-canonical D-amino acids on biofilms is a well-known phenomenon, first demonstrated when D-amino acids were identified as selfproduced disassembling factors in aging B. subtilis biofilms (Kolodkin-Gal et al, 2010;Oppenheimer-Shaanan et al, 2013). Non-canonical D-amino acids have been shown independently to inhibit biofilm formation and trigger biofilm disassembly in different model organisms (Hochbaum et al, 2011;Yu et al, 2012;Sanchez et al, 2013;Li and Wang, 2014;Si et al, 2014;Xing et al, 2015), and at concentrations that did not interfere with planktonic growth. Importantly, it was reported that B. subtilis NCIB 3610 (as well as many other natural isolates; Daligault et al, 2014) is carrying a defective allele of the dtd gene, involved in removal of D-amino acids from tRNA.…”
Section: Discussionmentioning
confidence: 99%
“…The destructive effect of non-canonical D-amino acids on biofilms is a well-known phenomenon, first demonstrated when D-amino acids were identified as selfproduced disassembling factors in aging B. subtilis biofilms (Kolodkin-Gal et al, 2010;Oppenheimer-Shaanan et al, 2013). Non-canonical D-amino acids have been shown independently to inhibit biofilm formation and trigger biofilm disassembly in different model organisms (Hochbaum et al, 2011;Yu et al, 2012;Sanchez et al, 2013;Li and Wang, 2014;Si et al, 2014;Xing et al, 2015), and at concentrations that did not interfere with planktonic growth. Importantly, it was reported that B. subtilis NCIB 3610 (as well as many other natural isolates; Daligault et al, 2014) is carrying a defective allele of the dtd gene, involved in removal of D-amino acids from tRNA.…”
Section: Discussionmentioning
confidence: 99%
“…D-amino acids may inhibit adhesion of bacterial cells to one another (45, 46). However, other studies starkly conflict with these results and suggest D-amino acids at 1 mM do not inhibit biofilm growth in S. aureus , B. subtilis , or S. epidermidis (47).…”
Section: Introductionmentioning
confidence: 99%
“…In certain external environmental conditions, planktonic cells attached to the substratum, which also refers to adhesion [29]. Two types of adhesion occur: reversible and irreversible adhesion.…”
Section: The Evolution Of Biofilmsmentioning
confidence: 99%